Caput Medusae due to portal hypertension in schistosomiasis mansoni - dos Santos, Vitorino Modesto (2017)
A 62-year-old Brazilian man who lived in endemic areas of tropical diseases had an episode of hematemesis associated with portal hypertension. He used to swim in natural ponds during childhood and developed the hepatosplenic form of schistossomiasis with moderate ascites, in addition to the characteristic features of abdominal Caput Medusae. The aim of the report is highlight the role of chronic liver disease and schistossomiasis.